SOCIAL PHILOSOPHY AS THEORETICAL GROUNDS OF IDEOLOGY - Vladimir G. Takhtamyshev (Advanced Engineering Research, 2011)
The ideological process of Modern age expressed in the advent of the specialized social and political ideology is investigated. The point that planning development prospects of the Russian society assumes coping with the unilateralism of the social and philosophical conceptions forming the theoretical basis for the future-oriented ideology is established.